The Women's Education in Islamic Educational Philosophy - Ibnaty Lailatul Arofah; Iqbal Arif; Khofifah Indrayani (Bulletin of Pedagogical Research, 2022)
This essay aims to examine and analyze the status of women in Islam, their right to pursue knowledge, and perspectives on women's education within the framework of Islamic educational philosophy. The study employs a library research method, supported by content analysis and constant comparative analysis approaches. Content analysis is utilized to explore written and printed materials, particularly those disseminated through mass media, in order to extract relevant insights. The findings reveal that, in the view of Islamic educational philosophy, women have consistently been granted the right to education. The Prophet Muhammad (peace be upon him) emphasized that seeking knowledge is a mandatory duty for all Muslims, regardless of gender. By underscoring this principle, the Prophet ensured that all avenues of knowledge were accessible to both men and women. This study contributes to the ongoing discourse on gender equality in education within the Islamic tradition and highlights the inclusive nature of knowledge pursuit in Islam.